Indicator of the efficiency of value added tax and income tax collection in Ecuador - José Ramírez-Álvarez; Paul Carrillo-Maldonado (CEPAL Review, 2020)
This paper outlines a methodology to measure the efficiency of revenue collection by tax administrations. The proposed methodology is aimed in particular at developing countries that do not have enough disaggregated information to measure tax gaps (registration, filing, veracity and payment) using traditional methods. The proposed indices are based on estimations of the structural balances of public finances, and rises in the indices can be interpreted as a comprehensive narrowing of tax gaps. The methodology is applied to Ecuador’s value added tax (VAT) and income tax, producing results that show that a more efficient tax administration leads to revenue growth.